2017
DOI: 10.1002/2017jb014164
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal changes of seismic attenuation caused by injected CO2 at the Frio‐II pilot site, Dayton, TX, USA

Abstract: A continuous active source seismic monitoring data set was collected with crosswell geometry during CO2 injection at the Frio‐II brine pilot, near Liberty, TX. Previous studies have shown that spatiotemporal changes in the P wave first arrival time reveal the movement of the injected CO2 plume in the storage zone. To further constrain the CO2 saturation, particularly at higher saturation levels, we investigate spatial‐temporal changes in the seismic attenuation of the first arrivals. The attenuation changes ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 50 publications
(76 reference statements)
0
11
0
Order By: Relevance
“…1B). First arrival travel time and amplitude changes, measured by the receivers at various depths in the observation well, allowed hour-by-hour monitoring of the growing CO 2 plume via the induced seismic velocity change (9,19) and seismic attenuation change (10). Each ray path had a unique response with those in the reservoir showing a clear delay in arrival time, which tended to stabilize after a few hours of injection (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1B). First arrival travel time and amplitude changes, measured by the receivers at various depths in the observation well, allowed hour-by-hour monitoring of the growing CO 2 plume via the induced seismic velocity change (9,19) and seismic attenuation change (10). Each ray path had a unique response with those in the reservoir showing a clear delay in arrival time, which tended to stabilize after a few hours of injection (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The concomitant changes in seismic velocities of the reservoir rocks can provide a basis for detecting and imaging CO 2 plumes (1). However, current approaches rely on active-source, time-lapse seismic techniques based on single-scattering reflected and transmitted waves (2)(3)(4)(5), and a combination of theoretical rock physics predictions (6), laboratory measurements (7,8), and field experiments (9,10) indicate that these can be insensitive to small changes in rock properties depending on CO 2 saturation state and other factors. Correspondingly, the derivation of CO 2 flow dynamics, such as local flow rate, CO 2 saturation, and CO 2 mass, from single-scattering seismic methods remains challenging.…”
mentioning
confidence: 99%
“…In the last example, we model the spatiotemporal attenuation effects on seismic waveforms by performing the time‐lapse wavefield simulations in a CO 2 injection geological model derived from the Frio‐II brine pilot CO 2 injection experiment (Daley et al, ; Zhu et al, , ). The time‐lapse models of both velocity and Q are retrieved from the Frio‐II CO 2 flow simulations using the rocks physics White's model (Daley et al, ).…”
Section: Numerical Examplesmentioning
confidence: 99%
“…At each time slice, the Q model and the velocity model at a high reference frequency (5 kHz) are shown in Figure and both parameters characterize the evolution of the CO 2 plume. An 800‐Hz Ricker wavelet source is excited at 1,657 m to match the dominant frequency of the Frio‐II field data (Daley et al, ; Zhu et al, ). The simulation time step is 0.02 ms.…”
Section: Numerical Examplesmentioning
confidence: 99%
“…CO 2 injection in deep reservoirs can be monitored through the spatiotemporal variations of P wave's first arrival. However, additional constraint on the location, extent, and saturation of CO 2 plumes can be obtained through the estimation of seismic attenuation changes derived from the frequency shift computed by local time‐frequency analysis (Zhu et al, ). It is shown that a crossplot method combining seismic attenuation and velocity changes applied to continuous seismic recordings during CO 2 injection at the Frio‐II brine pilot (Texas) is able to characterize the patch size and the saturation distribution within the CO 2 plume.…”
Section: Dynamic Fluid Injection and Substitutionmentioning
confidence: 99%